If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-1x + 2) = -7x + 44 Reorder the terms: -3(2 + -1x) = -7x + 44 (2 * -3 + -1x * -3) = -7x + 44 (-6 + 3x) = -7x + 44 Reorder the terms: -6 + 3x = 44 + -7x Solving -6 + 3x = 44 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -6 + 3x + 7x = 44 + -7x + 7x Combine like terms: 3x + 7x = 10x -6 + 10x = 44 + -7x + 7x Combine like terms: -7x + 7x = 0 -6 + 10x = 44 + 0 -6 + 10x = 44 Add '6' to each side of the equation. -6 + 6 + 10x = 44 + 6 Combine like terms: -6 + 6 = 0 0 + 10x = 44 + 6 10x = 44 + 6 Combine like terms: 44 + 6 = 50 10x = 50 Divide each side by '10'. x = 5 Simplifying x = 5
| 7c+8=-20 | | 9x-3-5x=13 | | 5-9x=105-44x | | 56x+16=0 | | 14x+13=85-5x | | 2(x+4)=x+1 | | 617mL+7.62L= | | 10x-6x-3=33 | | 34*2=x | | 4y-24+2y=0 | | -7x-2=8 | | x*x+3=20 | | 5x+24+2x=0 | | 34+97=x | | 3x^2-7=5x | | 5x+4y+23=0 | | .2x+5=8 | | -9x-2=-6x-14 | | 12=4-2y | | 4(2x-3)=28 | | 2x+193=11x-5 | | 162=3(x+6)(x+3) | | -45x^3+111x^2=0 | | -2w=-18 | | 58-3x=24x+19 | | (7x^2-4x+1)+(3x^2-9x-5)= | | 2x+1=5-4x | | -17p-11+2p^2=-2p^2+9p+3 | | 49-5x=13x+17 | | 7(x-2)=49 | | 15w+50=400 | | 20x^3+15x=0 |